Game meat hygiene in focus microbiology, epidemiology, risk analysis, and quality assurance - Paulsen, P. (Peter) (Wageningen Academic Pub., 2011)
Game meat is consumed world-wide. In most regions, it contributes only a small part to the overall meat and food supply, but for reasons of animal welfare and sustainability it is sometimes considered an alternative to meat from farmed animals. Despite differences in game species, ante mortem conditions (free-range or fenced; wild or semi-domesticated), hunting or harvesting procedures and further handling of the carcass, there are common requirements as regards meat safety and quality. Whereas meat hygiene and safety have been an issue in game meat for export/import for a long time, primary production, domestic supply and direct supply to the consumer have recently been addressed by legislation and these sectors still present unresolved questions and challenges. This book combines 24 contributions presenting the view of experts in game meat hygiene and quality. They address four main topics: i.e. hygiene and microbiology, epidemiology, risk assessment and management and muscle biology and meat quality. In addition to contributions on this topic by authors from eight European countries, a South African perspective is provided, thus representing the standpoint of a major game meat exporter. This volume is the first in a series on safety and quality assurance along the game meat chain, following a from forest to fork approach and is targeted at scientists in academia and industry, graduate students as well as at governmental officials in veterinary public health and food safety.